Effect of electromagnetic casting process on microstructure and properties of AZ31 magnesium alloy. (2nd November 2019) - Wang, Qiwei; Li, Dan; Chen, Dexin; Wang, Xiaoming; Chang, Qing; Han, Guofeng; Zhu, Yunlei; Zhu, Sheng; Li, Wei
ABSTRACT: In this paper, AZ31 magnesium alloy is cast by applying the semi-continuous casting process with a low-frequency electromagnetic field. By studying the influence of electromagnetic field frequency, excitation current intensity and casting velocity on the microstructure and mechanical properties, the optimum process under oil-slip electromagnetic casting conditions was determined to improve the degree of grain refinement, yield strength, elongation and tensile strength of AZ31 alloy. An improved microstructure refining effect and higher hardness can be obtained with a current intensity af 60 A. The microstructures and mechanical properties obtained for different casting velocities of V = 200 mm/min and V = 230 mm/min at processing parameters of f = 30 Hz and I = 120 A were compared. Our results suggest that a higher casting speed does not lead to grain refinement or improved mechanical properties. Frequency